Effect of isothermal aging on the pitting corrosion resistance of UNS S82441 duplex stainless steel based on electrochemical detection. (April 2015) - Zhang, Ziying; Zhao, Hui; Zhang, Huizhen; Yu, Zhishui; Hu, Jun; He, Liang; Li, Jing
Highlights: Effect of isothermal aging on the pitting corrosion resistance of UNS S82441 DSS was investigated. Austenite phase shows a priority to be attacked by pits for the as-annealing specimen. Pitting corrosion resistance of test specimens decreases with an increasing aging time. Pits initiated in the chromium-depleted zones after aging. The corrosion type evolves from pitting corrosion into general corrosion ultimately. Abstract: The effect of isothermal aging at 700 °C for various times on the pitting corrosion behavior of UNS S82441 duplex stainless steel was investigated using a combination of potentiodynamic polarization and potentiostatic critical pitting temperature techniques. The results show that the austenite phase of the as-annealed specimen is susceptible to pitting. With increasing aging time, the resistance of test specimens to pitting corrosion decreases. Additionally, pitting transfers from the austenite phase into chromium-depleted zones. Finally, the corrosion evolves from pitting corrosion into general corrosion as the holding time extends to 48 h.